Diversity judgments democratizing judicial legitimacy - Brooks, Roy L. 1950- (Cambridge University Press, 2022)
The US Supreme Court's legitimacy-its diminishing integrity and contribution to the good of society-is being questioned today like no other time in recent memory. Criticisms reflect the perspectives of both 'insiders' (straight white males) and 'outsiders' (mainly people of color, women, and the LGBTQ community). Neither perspective digs deep enough to get at the root of the Court's legitimacy problem, which is one of process. The Court's process of decision-making is antiquated and out of sync with a society that looks and thinks nothing like the America of the eighteenth century, when the process was first implemented. The current process marginalizes many Americans who have a right to feel disenfranchised. Leading scholar of jurisprudence Roy L. Brooks demonstrates how the Court can modernize and democratize its deliberative process, to be more inclusive of the values and life experiences of Americans who are not straight white males